Integration of music-based game approaches with wearable devices for hand neurorehabilitation: a narrative review - (:unkn) unknown (BioMed Central, 2024)
Background. Restoring hand functionality is critical for fostering independence in individuals with neurological disorders. Various therapeutic approaches have emerged to address motor function restoration, with music-based therapies demonstrating notabl...
Keywords: Neurorrehabilitación; Dispositivos portátiles